Aid that works : successful development in fragile states - Manor, James (Directions in development (Washington, D.C.), 2007)
Research in recent years on aid effectiveness shows that significant obstacles in fragile states - insecurity, poor governance and weak implementation capacity - usually prevent aid from achieving the desired results in these environments. This study investigates the attributes and effectiveness of donor-supported programmes and projects that worked well under difficult conditions in fragile states. Presented in this study are nine development initiatives in six less developed countries - Afghanistan, Cambodia, Mozambique, Sierra Leone, Timor Leste and Uganda. The cases show that development i.